MENGEMBANGKAN KEBIJAKAN PUBLIK UNTUK MENINGKATKAN KUALITAS PEDIDIKAN DI DAERAH TERPENCIL - Joni Hendriansah; Riqo Ayatillah; Hayat, Hayat (Triwikrama: Jurnal Ilmu Sosial, 2025)
Education in remote areas is still lagging behind compared to urban areas. Limited access, infrastructure and human resources are the main factors inhibiting educational progress in the region. This journal aims to discuss strategies for improving the quality of education in remote areas through the use of technology and multi-stakeholder collaboration. This research uses qualitative methods with a case study at a school in a remote area. The research results show that the use of technology and multi-stakeholder collaboration can improve the quality of education in remote areas. Utilization of technology can be done using e-learning, learning videos, and simulations. Multi-stakeholder collaboration can be carried out between government, schools, communities and non-governmental organizations. The findings of this research provide important implications for educational policy and practice in remote areas. The government needs to increase funding allocations for providing infrastructure and technology in schools in remote areas. Schools need to develop learning programs that utilize technology and collaborate with various parties to improve the quality of education. The community needs to be actively involved in supporting education in remote areas.